2020
DOI: 10.1007/s40122-020-00156-6
|View full text |Cite
|
Sign up to set email alerts
|

Results of Mirogabalin Treatment for Diabetic Peripheral Neuropathic Pain in Asian Subjects: A Phase 2, Double-Blind, Randomized, Placebo-Controlled, Study

Abstract: Introduction: Almost one-quarter of Asian patients with diabetes experience diabetic peripheral neuropathic pain (DPNP), which may be associated with moderate or severe levels of pain, insomnia, mood disorders, and worsened quality of life. Current treatments are generally ineffective and may be poorly tolerated. We evaluated mirogabalin as a treatment for DPNP in Asian subjects. Methods: This phase 2, randomized, doubleblind, controlled study was conducted in Japan, Enhanced Digital Features To view enhanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…Thrombospondins are matrix proteins involved in synaptogenesis [ 45 ], bind to α2δ-1, are upregulated after peripheral nerve injury, and disrupt intracellular Ca2 + signaling due to the interaction with this auxiliary subunit of the calcium channel [ 46 ]. A better understanding of these phenomena is of the utmost importance to clarify the mechanism of action of α2δ-1 ligands such as gabapentin, pregabalin, and the newest mirogabalin [ 47 , 48 ], which is reportedly endowed with neuropsychiatric activities during chronic pain states [ 49 , 50 , 51 ], clinical conditions in which, for instance, these drugs are often inappropriately used in non-communicative patients [ 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thrombospondins are matrix proteins involved in synaptogenesis [ 45 ], bind to α2δ-1, are upregulated after peripheral nerve injury, and disrupt intracellular Ca2 + signaling due to the interaction with this auxiliary subunit of the calcium channel [ 46 ]. A better understanding of these phenomena is of the utmost importance to clarify the mechanism of action of α2δ-1 ligands such as gabapentin, pregabalin, and the newest mirogabalin [ 47 , 48 ], which is reportedly endowed with neuropsychiatric activities during chronic pain states [ 49 , 50 , 51 ], clinical conditions in which, for instance, these drugs are often inappropriately used in non-communicative patients [ 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…18 Three randomised, double-blind, controlled studies were conducted to gauge the efficacy and tolerability of mirogabalin in DPNP patients. 16,19,20 Overall, these studies showed promising results that need to be confirmed in further trials.…”
mentioning
confidence: 71%
“…A similarlydesigned phase 2 study showed a decreased average daily pain score and sleep interference score [31]. In another phase 2 study, mirogabalin (5,10,15,20, and 30 mg twice a day) decreased the average daily pain score, average daily sleep-interference score, and ADRs [32]. In addition, mirogabalin 10 or 15 mg twice a day showed long-term (52 wk) safety and efficacy in patients with DPNP [33].…”
Section: (3) Patients With Dpnpmentioning
confidence: 95%
“…The initial dose for adults without renal dysfunction is recommended starting from 5 mg, given orally twice a day. The dose is gradually increased by 5 mg, at an interval of at least a week, to 15 mg at the 3rd week [2,3,[25][26][27][28][29][30][31][32][33].…”
Section: Clinical Application Of Mirogabalin 1) Pharmacokineticsmentioning
confidence: 99%